Promoted Selective Non-Catalytic Reduction: Prospective Technology for Nitrogen Oxide Reduction - Khandoker Abu Hossain; Mohammad Nazri Mohd-Jaafar; Farid Nasir Ani (ASEAN Journal of Chemical Engineering, 2004)
Promoted selective non-catalytic reduction (SNCR) of nitric oxide (NOx) has been studied experimentally by injecting aqueous urea solution with and with;ut additive in a pilot-scale diesel-fired tunnel furnace at 3-4 % excess oxygen level and with low ppm of baseline NO-, ranging from 65 to 75 ppm within the investigated temperature range. The tests were carried out using commercial grade urea as NO- reducing agent and commercial grade sodium carbonate (Na2CO3) as additive. The f~rnace simulated the small-scale combustion systems where (a) operating temperatures are usually within 973-1,323 K and (b) NO-, emission level remains below 100 ppm. In the SNCR process with 5% urea solution, at normalized stoichiometric ratio (NSR) of 4, as much as 54% reduction was achieved at 1,128 K; while in the promoted SNCR process using Na2C03 additive, NO-, reduction improved to as much as 69% at 1,093 K In addition, the effective temperature window as well as peak temperature of NO-, reduction shifted towards lower temperatures in promoted SNCR These results were significant especially for the investigated level of baseline NO-. The ammonia slip measurements showed that in both cases the slip was below 16 ppm at an NSR of 4 and an optimum temperature of NO, reduction. The investigations demonstrated that urea-based promoted SNCR may be used for small-scale combustion applications and that commercial grade Na2C03 is a potential additive.